THE AL-QUR'AN IN EDUCATIONAL DEMENSIONS - Zailani, Zailani (Proceeding International Seminar of Islamic Studies, 2022)
This research is about the Qur'an in its educational dimension. How does the Qur'an talk about the intricacies of education, which include the meaning of Iqra in the Qur'an, what potential humans have for the learning process, and what is the character of the human heart, so that the full meaning of Iqra can be known? Another goal is to find out in detail what potential human beings have and the basic character of the human heart. This research is qualitative in nature, with a library research approach. As for data collection, use all documents related to research materials, including books, manuscripts, and interviews. The results obtained are that, when iqra is interpreted by reading in a broader sense, it contains the meaning of understanding, analyzing, and the presence of continuity between thought and remembrance. Humans have four potentials that can be used for needs in education, namely: mind, heart, lust, and lust. The four potentials have different characters and ways of working. Satan often uses lust to direct people according to his will. As for the mind and heart as a way prepared by God to know Him better